Effects of Dietary Histidine Levels on Growth Performance, Feed Utilization, and Expression of Related Genes of Juvenile Hybrid Grouper Epinephelus fuscoguttatus ♀×Epinephelus lanceolatus♂. (23rd March 2022) - Taj, Sehrish; Ma, Lei; Wu, Xiaoyi; Ye, Bo; Geng, Lina; Zhou, Zhiyu; Wang, Xiao; Mu, Wei
Abstract : Histidine (His) is a ♀nutritionally significant amino acid and plays a key regulatory role in growth-related cellular functions. The present study was conducted to assess the effects of dietary His levels on hybrid grouper growth performance, feed utilization, and related gene expression. Seven isoenergetic, isoproteic, and isolipidic diets were made up to contain 6.9, 7.2, 8.6, 9.2, 10.7, 11.1, and 11.7 g/kg dietary His levels. The results revealed that protein productive value (PPV), feed efficiency (FE), and weight gain (WG) were increased with an increase in dietary His levels up to 10.7 g/kg. Based on the analysis of the second-order polynomial model, the optimal dietary His level for maximum PPV, WG, and FE was 9.24, 9.62, and 9.47 g/kg, respectively. The gut morphology was affected by various dietary His levels. Furthermore, dietary His levels can affect the relative mRNA levels of growth hormone receptor (GHR1) insulin-like growth factor1 (IGF1), the target of rapamycin (TOR), tumor necrosis factor α (TNF- α ), and S6 kinase1 (S6K1). Dietary 9.2 g/kg His revealed a high level of Nrf2 expression in the head kidney. Generally, the optimal dietary His level for the best growth performance of hybrid grouper was found to be 9.62 g/kg dry matter or 21.08 g/kg dietary protein.